Herbs: Ginseng and Eleuthero - Latta, Susan A. (My University, 1999)
This publication explains how ginseng and eleuthero was used and describes modern uses for the plants.
MF2376_1999_03
Keywords: MF2376; Health and Safety; Lawn and Garden; MF